2018
DOI: 10.1111/jnc.14450
|View full text |Cite
|
Sign up to set email alerts
|

High‐mobility group box 1 in Parkinson's disease: from pathogenesis to therapeutic approaches

Abstract: Parkinson's disease (PD) presents the second most common neurodegenerative disorder with largely unknown pathogenesis and inefficient therapeutic management. Accumulating data indicate that neuroinflammation, autophagy impairment, α-synuclein aggregation, and mitochondrial dysfunction may contribute to PD onset; however, the molecular mechanisms underlying these pathophysiological processes are still under elucidation. Interestingly, recent evidence has indicated that High-mobility group box 1 (HMGB1), a DNA-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 51 publications
0
37
0
Order By: Relevance
“…HMGB1 has been found to be closely related to the inflammatory diseases (Lu et al, 2012). It can be actively secreted by inflammatory cells and released by necrotic cells (Angelopoulou et al, 2018). After that HMGB1 can bind to various transmembrane receptors including TLR2, TLR4, and TLR9, and increase DNA-binding capacity of several transcription factors, such as p53 as well as NF-kB (Martinotti et al, 2015), ultimately leading to inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 has been found to be closely related to the inflammatory diseases (Lu et al, 2012). It can be actively secreted by inflammatory cells and released by necrotic cells (Angelopoulou et al, 2018). After that HMGB1 can bind to various transmembrane receptors including TLR2, TLR4, and TLR9, and increase DNA-binding capacity of several transcription factors, such as p53 as well as NF-kB (Martinotti et al, 2015), ultimately leading to inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the dynamics of HMGB1 translocation and activity is an important factor that will be helpful in assessing the disease pathology. Arrays of studies have repeatedly reported the release of HMGB1 from nuclei in a range of neurological disorders including epilepsy (Fu et al 2017;Zhao et al 2017;Angelopoulou et al 2018;Sun et al 2018). The nuclear to cytosol translocation of HMGB1 and its release from neural cells is associated with posttranslational modifications and is implicated in the epileptic seizure generation (Fig.…”
Section: Hmgb1 Dynamics During Epilepsymentioning
confidence: 99%
“…Neuroinflammation due to an overactivated and/or chronically activated state of microglia is another source of excessive and uncontrolled release of free radicals. Molecular mechanisms underlying these pathophysiological processes are still under evaluation, but recent evidence comes from studies on high-mobility group box 1 (HMGB1) [11], mammalian target of rapamycin (mTOR) signaling [12], and the nuclear factor, erythroid 2 like 2 (Nrf2) [13], among others. Recent breakthroughs from genetic studies revealed that lysosomal system dysfunction is one of the earliest pathogenetic mechanisms.…”
Section: Introductionmentioning
confidence: 99%